PENGARUH KEMAMPUAN SUMBER DAYA MANUSIA DAN MOTIVASI KERJA TERHADAP KINERJA ORGANISASI - Syifa, Tania Aulia (Jurnal Kewirausahaan dan Inovasi, 2023)
The objective of this research is to identify the partial and simultaneous effects of human resource capability and work motivation on the organizational performance of Sasirangan MSME in Banjar Regency. The MSME is one of the production businesses that have survived for a long time. In order to ensure high performance, their human resource must be well governed. This quantitative explanatory research explains the influences of the variables through hypothesis testing. Using saturated sampling, 112 managers of Sasirangan MSME in Banjar Regency were selected as the sample. The data was harvested from interviews and questionnaires and was analyzed using data quality test, classical assumption test, and multiple linear regression. This study finds that (10 human resource capability and work motivation simultaneously have positive and significant effects on the organizational performance of the MSME in the regency, that (2) human resource  capability partiall has a negative and significant effect on the organizational performance, and that (3) work motivation partially has a positive and significant effect on the organizational performance of the MSME in the regency.